‘I Feel Comfortable Enough and Trust the People Around Me to Be Able to Open Up’: Exploring How Mental Health Community Support Groups Help Older Men Navigate Mental Health and Masculinities in Later Life - Alex Vickery (Journal of Long-Term Care)
Context: The use of community support groups and peer support are expanding across mental health and older people’s services, however, there is a lack of evidence on how such support may be beneficial to older men who might struggle with aspects of traditional mental health help seeking due to male identity, ageing and isolation.